Reconstructing Phylogenies of Alocasia spp. (Araceae) Distributed in Indonesia for Conservation Prioritization: Reconstructing phylogenies of Alocasia spp. (Araceae) - Arief Priyadi; Ni Putu Sri Asih; Ina Erlinawati (Journal of Tropical Life Science, 2022)
Phylogenetic analysis is beneficial to plant conservation prioritization. Conservation does not only deal with species but also their evolutionary potential. A phylogenetic tree is usually reconstructed by using the alignment of DNA sequences. However, Â with the availability of megatrees, subsetting with a list of species of concern is possible. Here we reconstructed a list of 53 Alocasia spp. (Araceae) from Indonesia and adjacent regions using available megatrees and publicly available DNA sequences in the GenBank. The result showed placed and unplaced Alocasia spp. on the terminal nodes of reconstructed phylogenetic trees. The unplaced species show that publicly available DNA sequences are not yet available, therefore should be prioritized for sequencing. The placed species in the phylogeny could be used for conservation prioritization of these Alocasia spp.